PENGGUNAAN METODE COOPERATIVE LEARNING TIPE MAKE-A MATCH DALAM MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR - Lestari, Yulita Dwi (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
This research is classroom action research using cooperative learning method type make a match which is carried out in 2 cycles and each cycle 3 meetings, the object of this research is class IV SD Negeri 1 Gisting with the number of students as many as 28 people in natural science subjects . observation to observe directly student learning activities during the learning process, test learning outcomes to obtain data on the progress of learning outcomes, documentation to obtain data about the teaching and learning process of Gisting Elementary School 1. The analysis used by researchers is to use simple statistical formulas, namely quantitative analysis and qualitative analysis. From the results of the analysis it can be seen the results that student activity increased overall 7.6% from 78.75% in the first cycle to 85.74% in the second cycle, then the learning outcomes increased 36% from 68% in the first cycle to 85% in cycle II. Based on these data, it can be concluded that by using cooperative learning methods the type of make-a mach has a positive contribution in the teaching and learning process.